Faktor-Faktor yang Mempengaruhi Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening - Suryani, Cahya; Handajani, Lilik; Effendy, Lukman (E-Jurnal Akuntansi; Vol 30 No 7 (2020)DO - 10.24843/EJA.2020.v30.i07.p18, 2020)
This study aims to analyze the factors that affect Company Value by using profitability as an Intervening Variable. The research data was obtained from the annual financial statements of the banking sub-sector companies listed on the Indonesia Stock Exchange in 2016 to 2018. Data analysis used path analysis techniques. The analysis shows that the intellectual capital variable measured by VAIC TM has no effect on profitability that is proxied by ROE and the value of the company is measured using the total amount of assets, this is because there are still many companies that do not pay attention to intellectual capial on their companies, companies tend to pay more attention tangible assets while Good corporate governance which is proxied by the number of audit committees only has a significant effect on firm value while profitability (ROE) has a significant effect on firm value. Keywords: Company Value; Profitability; Intellectual Capital; Good Corporate Governance.